2019
DOI: 10.1111/os.12597
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Percutaneous Screw Fixation and Plate Fixation via Sinus Tarsi Approach for Calcaneal Fractures: An 8–10‐Year Follow‐up Study

Abstract: Objective To assess the long‐term outcomes after percutaneous reduction (PR) and screw fixation versus plate fixation via the sinus tarsi approach (STA) for displaced intra‐articular calcaneal fractures (DIACF). Methods This retrospective study included a total of 150 patients (June 2008–August 2011), comprising 85 men and 65 women (mean age, 38.4 years), who were assigned to the PR group or the STA group. The inclusion criteria were DIACF (>2 mm) including Sanders type II and III, closed fracture, unilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…The authors found no statistically significant difference in the postoperative AOFAS scores. In another clinical study reported by Weng et al, [23] similar results were achieved. In our study, there was no statistically significant difference between the two groups in terms of the AOFAS, MFS, and the SF-36 scores at the first, second, and third postoperative years.…”
Section: R E T R a C T I O Nsupporting
confidence: 68%
“…The authors found no statistically significant difference in the postoperative AOFAS scores. In another clinical study reported by Weng et al, [23] similar results were achieved. In our study, there was no statistically significant difference between the two groups in terms of the AOFAS, MFS, and the SF-36 scores at the first, second, and third postoperative years.…”
Section: R E T R a C T I O Nsupporting
confidence: 68%
“…1). We totally identified 736 unique studies after searching the electronic databases, and only seven RCTs were finally included in the meta-analysis [19][20][21][22][23][24][25]. All seven studies compared the effectiveness of cannulated screw fixation and plate fixation for DIACFs.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…The CSF group contained 457 patients, and the plate fixation group contained 445 patients. Four RCTs [20,21,24,25] included Sanders types II, III, and IV, and three RCTs [19,22,23] only included Sanders types II and III. Details of included studies are presented in Table 1.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations